2017
DOI: 10.1016/j.celrep.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsic Transcriptional Program Underlying Synaptic Scaling during Activity Suppression

Abstract: Summary Homeostatic scaling allows neurons to maintain stable activity patterns by globally altering their synaptic strength in response to changing activity levels. Suppression of activity by blocking action potentials increases synaptic strength through an upregulation of surface AMPA receptors. Although this synaptic up-scaling was shown to require transcription, the molecular nature of the intrinsic transcription program underlying this process and its functional significance have been unclear. Using RNA-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 71 publications
11
71
0
Order By: Relevance
“…5e). In agreement with our data, it was previously reported that surface abundance of Nptx1 increases after 24 hours of TTX treatment and that inhibition of Nptx1 expression blocks synaptic upscaling 56 .…”
Section: Homeostatic Plasticity Induces Reorganization Of the Neuronasupporting
confidence: 94%
See 2 more Smart Citations
“…5e). In agreement with our data, it was previously reported that surface abundance of Nptx1 increases after 24 hours of TTX treatment and that inhibition of Nptx1 expression blocks synaptic upscaling 56 .…”
Section: Homeostatic Plasticity Induces Reorganization Of the Neuronasupporting
confidence: 94%
“…During synaptic upscaling total and surface abundance levels of Nptx1 increased (Fig. 5e), which recapitulates previous findings achieved with orthogonal approaches 56 . For synaptic downscaling, our data on Nptx2 (Fig.…”
Section: Homeostatic Plasticity Induces Reorganization Of the Neuronasupporting
confidence: 89%
See 1 more Smart Citation
“…It would be interesting to know if the genes repressed by singing are induced by hyperpolarization or neuronal inactivity. Intriguingly, blocking neuronal activity in cultured mouse cortical neurons induced the expression of many genes (Schaukowitch et al, 2017), suggesting that a gene expression program that responds to neuronal inactivity exists in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that activity-regulated transcription would be required for firing rate homeostasis because it is required for several forms of homeostatic plasticity that could regulate firing rate. First, synaptic scaling, a multiplicative homeostatic change in the number of AMPA receptors at synapses (Turrigiano et al, 1998), is impaired by both acute blockade of transcription and by loss of specific activity-regulated genes (ARGs), including Arc, Nptx1, Plk2 , and Homer1a (Chowdhury et al, 2006; Diering et al, 2017; Hu et al, 2010; Ibata et al, 2008; Schaukowitch et al, 2017; Seeburg et al, 2008; Shepherd et al, 2006). In addition, activity-regulated transcription also homeostatically regulates excitatory/inhibitory (E/I) balance, or the relative strengths and numbers of excitatory and inhibitory synapses.…”
Section: Introductionmentioning
confidence: 99%